Spillover Effects of COVID-19 on Essential Chronic Care and Ways to Foster Health System Resilience to Support Vulnerable Non-COVID Patients: A Multistakeholder Study - Yoon, Sungwon (ELSEVIER SCIENCE INC, 2022)
10.1016/j.jamda.2021.11.004